(3QhVI GdYdeGAs - (3MSjf Hf jMji GdHNGQj GdRfOhSJj GdMfaj, CHh Ydjs
(3ChdgG (B:s
(3jHOC HGdHGH GdChd ai aVd GdYde hGdYdeGA s
(3BNQgG (B:s
(3JeJ hGdMeO ddg hMOg hUdi Gddg Ydi SjOfG eMeO hBdg hUMHg hSde s
(3GdfSNI HgG MhGTs
(3fSNI KGfjIs
(3eUOQ GbJfGA GdCUd (B:s
(3CMeO GdKGdK s
Keywords: (3Gdabg GdMfajs